Tanggung Jawab Para Pihak Setelah Pelaksanaan Lelang Tanah Kas Desa: Studi Kasus di Desa Cangaan Kabupaten Bojonegoro - Megawati, Tiyas Putri; Fahmida, Faizah Nur; Ramadhanti, Aulia Dwi (Acten Journal Law Review, 2024)
Auction is a sale that is open to the public with written and/or oral price offers and guided by an auction official. This is different from what happened in Cangaan Village where the Village Treasury Land auction was carried out without an auction official and was carried out using a lottery system. The uniqueness of the implementation of this auction then became the basis for the author to further examine and find out the extent of the differences in the implementation of the Village Treasury Land auction in Cangaan Village, the rights and obligations arising from the parties involved and the things that must be done after the auction was carried out. The research method used is normative juridical by examining primary legal sources and related secondary legal sources. After examining the case of the Village Treasury Land auction in Cangaan Village, it was found that the village treasury land auction fell into the third version of the auction, namely what was offered in the auction was an opportunity to work together. In this type of auction, the legal act that arises is a lease between the Village Government and the auction winner. This results in the emergence of rights and obligations of the parties on the basis of a post-auction lease relationship. Keywords: Auction; Village Treasury Land; Responsibility